IMPLEMENTATION OF MULTICULTURAL VALUES IN ISLAMIC RELIGIOUS EDUCATION - Ahmad Fauzi (Universitas Islam Malang, 2022)
This study aims to define, analyze and construe (1) the values of any Multicultural Islamic Religious Education in the implementation of learning at Ma'had Darul Hikmah and Ma'had Al Qolam (2) Carrying out of the learning process of Multicultural Islamic Religious Education in Ma'had Darul Hikmah and Ma'had Al Qolam, (3) Multicultural Religious Learning Model in Ma'had Darul Hikmah and Ma'had Al Qolam. Based on the research results, it was found that multicultural values, the implementation of the learning process and the multicultural learning model both in Ma'ad Darul Hikmah and Ma'had Al Qolam. First, the values of Multicultural Islamic Religious Education in the implementation of the second lesson of ma'had, explicitly (1) introduction, (2) moderate, (3) tolerance, (4) please help, (5) harmony, (6) empathy, ( 7) compassion, (8) togetherness, (9) respect for differences, (10) willing to sacrifice, (11) tolerance, (12) brotherhood, (13) equality, (14) justice. And (15) Khusnuddhon. Second, the implementation of the learning process (1). Learning design follows the ROPEZ model (review, overview, presentation, exercise, summary). (2) The implementation of the learning process is called Ta'lim which is carried out after Fajr and after Maghrib. Learning resources comprise: messages, people, materials, tools, techniques and backgrounds (3) Evaluation of Learning Outcomes is carried out at the beginning of each semester and at the end of each level, carried out in written form and part of the practice. Third, the Multicultural Learning Model at Ma'had Al Qolam follows the following sequence: (1) Preparation of Management Guidelines / Revision of Ma'had Management Guidelines (2). Design of Ma'had Curriculum, (3) Arrangement of Santri in Rooms, Mabna and Class (4) Making Prota and Learning Encourages, (5) Teaching and Learning Activities (6). Evaluation at the end of the school year.Keywords:Ã‚Â Multicultural, Learning, Ma'had